Деякі проблеми тимчасового вилучення та арешту майна як заходів забезпечення кримінального провадження - Гловюк, Ірина Василівна; Гловюк, Ирина Васильевна; Glovjuk, Irina (My University, 2013)
The article is dedicated to the research of problematic issues of exercise of temporary seizure of property and arrest of property as means for ensuring criminal proceedings considering relevant judicial practices. Author mentioned and justified his point of view regarding incorrectness of the normative definition of seizure. Author also indicated whitespaces of the regulatory definition of arrest of property in the aspect of objects that may be the subject for the arrest. Proposals for amendments and additions to the part 1 of the Art. 167 of the Criminal Procedure Code regarding the definition of «temporary seizure of property» and part 1 of the Art. 170 of the Criminal Procedure Code regarding the scope of persons whose property may be arrested have been made.
Гловюк І. В. Деякі проблеми тимчасового вилучення та арешту майна як заходів забезпечення кримінального провадження / І. В. Гловюк // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 520-528.
Keywords: тимчасове вилучення майна; арешт майна; підозрюваний; речові докази; обшук; огляд; временное изъятие имущества; арест имущества; подозреваемый; вещественные доказательства; обыск; осмотр; temporary seizure of property; arrest of property; suspect; physical evidence; search; inspection.